Fusarium oxysporum f. sp. vasinfectum 5.8s rRNA gene and adjacent ITS1 and ITS2 regions - Salvatore Moricca; Takao Kasuga; Keith Mitchelson; Alessandro Ragazzi (Fungal Genetics Reports, 1995)
Fusarium oxysporum, Schlecht ex Fr. is a phytopathogenic fungus causing wilting or yellows disease on a variety of plant species throughout the world. It is categorized in formae speciales according to pathotypic variation and physiological character (Messiaen and Cassini, 1981 Fusarium:- Diseases, Biology and Taxonomy pp.427-445). The F. oxysporum forma specialis vasinfectum (Atk.) Snyder and Hansen is pathogenic on cotton (Gossypium spp.) on which it causes severe damage to susceptible races. We report here the DNA sequence of the 5.8S rRNA gene and flanking intergenic transcribed spacers of F. oxysporum forma specialis vasinfectum. DNA was isolated from mycelial cultures from three virulent isolates collected from single cotton plants from geographically distant sites in Bié, Cuanza Norte and Cuanza Bul regions of Angola (Ragazzi, 1992 J. Pl. Disease Protect. 99:499-504).